Two-Class Voting: A Mechanism for Conflict Resolution - Maug, Ernst; Yilmaz, Bilge (American Economic Review, 2002)
We discuss two-class voting procedures where voters are divided into classes and a separate majority is required in each class. Examples include Chapter 11 bankruptcy proceedings and some political mechanisms. We investigate how voting mechanisms aggregate information dispersed among voters when voters have conflicts of interests as well as different information regarding a proposal. We find that two-class voting provides a significant improvement over one-class voting in all situations where voters have significant conflicts of interests, and where the voters are relatively evenly divided between interest groups. However, two-class voting is inefficient absent conflicts of interests.